2015
DOI: 10.1080/07399332.2015.1066788
|View full text |Cite
|
Sign up to set email alerts
|

Post-Partum Depression, Personality, and Cognitive-Emotional Factors: A Longitudinal Study on Spanish Pregnant Women

Abstract: In this study, our purpose was to examine whether personality and cognitive factors could be related to post-partum depression (PPD), mediated by anxiety, in Spanish women. Women were evaluated for personality and cognitive factors after the first trimester, for anxiety in the third trimester, and for PPD 4 months after childbirth. A structural equation model revealed that personality and cognitive factors were associated with anxiety and PPD as predictors. Neuroticism and extroversion proved to be the most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 56 publications
14
28
0
1
Order By: Relevance
“…ese findings are also supported by those results of a crosssectional study carried out by Peñacoba-Puente et al [22] up on 209 women in Madrid, Spain, by using the Beck Depression Inventory II. ey said that there was a significant negative correlation between progesterone level and depression scores.…”
Section: Journal Of Environmental and Public Healthsupporting
confidence: 81%
See 1 more Smart Citation
“…ese findings are also supported by those results of a crosssectional study carried out by Peñacoba-Puente et al [22] up on 209 women in Madrid, Spain, by using the Beck Depression Inventory II. ey said that there was a significant negative correlation between progesterone level and depression scores.…”
Section: Journal Of Environmental and Public Healthsupporting
confidence: 81%
“…Peñacoba-Puente et al [22], in their study revealed that postpartum symptoms of depression and anxiety were all signi cantly correlated with each other. is agrees with our nding that 21.2%, about two thirds of the su ering females, have comorbid depression and anxiety.…”
Section: Discussionmentioning
confidence: 89%
“…In this respect, recent studies reported the presence of psychopathological symptoms through the SCL-90-R during pregnancy to be related with postpartum depression [ 53 , 54 ]. More specifically, depression, anxiety, and stress during pregnancy have been related with negative pregnancy outcomes, including postpartum depression [ 55 , 56 ]. Psychological stress during pregnancy has been related to postpartum depression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies evidenced that more emotionally stable women were at lower risk for depressive and anxiety symptoms and disorders during pregnancy and after delivery [54][55][56][57][58][59][60]. Some studies also found that higher levels on other Big Five personality traits-especially extraversion [55,[61][62][63] and conscientiousness [55,63]-were associated with a lower risk for peripartum depression or anxiety. However, the predictive role of individual Big Five personality traits for changes in depressive, anxiety, and stress symptoms during pregnancy and after delivery remains an open question.…”
Section: The Role Of Maternal Personalitymentioning
confidence: 99%